Acute and short-term response to different loading conditions during resisted sprint training - Bachero-Mena, B.; Sánchez-Moreno, M.; Pareja-Blanco, F.; Sañudo, B. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To analyze the acute and short-term physical and metabolic responses to resisted sprint training with 5 different loading conditions (0%, 20%, 40%, 60%, and 80% body mass). Methods: Fifteen male participants performed 8×20-m sprints with 2-minute rests between sprints with 5 different loading conditions. Subjects performed a battery of tests (creatine kinase and lactate concentrations, countermovement jump, 20-m sprint, and isokinetic knee extension and flexion contractions) at 3 different time points (preexercise [PRE], postexercise [POST], and 24-h postexercise [POST24H]). Results: Results revealed significant increases in blood lactate for all loading conditions; however, as sled loadings increased, higher blood lactate concentrations and increments in sprint times during the training session were observed. Significant increases in creatine kinase concentration were observed from PRE to POST24H for all loading conditions. Concerning physical performance, significant decreases in countermovement-jump height from PRE to POST were found for all loading conditions. In addition, significant decreases in 20-m sprint performance from PRE to POST were observed for 0% (P=.05) and 80% (P=.02). No significant differences with PRE were observed for the physical-performance variables at POST24H, except for 20% load, which induced a significant decrease in mean power during knee flexion (P=.03). Conclusions: These results suggest that the higher the load used during resisted sprint training, the higher the physical-performance impairments and metabolic response produced, although all loading conditions led to a complete recovery of sprint performance at POST24H.